2009
DOI: 10.1002/smll.200900345
|View full text |Cite
|
Sign up to set email alerts
|

Greatly Improved Blood Compatibility by Microscopic Multiscale Design of Surface Architectures

Abstract: A multiscale architecture with interlaced submicrometer ridges and nanoprotrusions is built on a polydimethylsiloxane (PDMS) surface by a combination of self‐assembly, soft lithography, and physical treatment (see picture). The multiscale structure reduces activated‐platelet adhesion under flow conditions, which is significant for the development of blood‐contacting materials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
70
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(72 citation statements)
references
References 24 publications
(23 reference statements)
1
70
0
1
Order By: Relevance
“…Platelet adhesion assays showed that the resulting surface exhibited good platelet resistance under flow. [79] Milner et al built nanoscale square pillars on a polyether(urethane urea) (PUU) surface and found that at low shear stress platelet adhesion on this surface was significantly suppressed. [80] It has also been suggested that optimization of chemical properties together with topography could provide surfaces with novel functionality.…”
Section: Stimuli-responsive Polymers and Diblock Copolymers For Surfamentioning
confidence: 99%
“…Platelet adhesion assays showed that the resulting surface exhibited good platelet resistance under flow. [79] Milner et al built nanoscale square pillars on a polyether(urethane urea) (PUU) surface and found that at low shear stress platelet adhesion on this surface was significantly suppressed. [80] It has also been suggested that optimization of chemical properties together with topography could provide surfaces with novel functionality.…”
Section: Stimuli-responsive Polymers and Diblock Copolymers For Surfamentioning
confidence: 99%
“…From the biomimetic viewpoint, a hierarchical structure composed of microand nanoscale components may provide a more suitable surface topography for cell functions as it can better mimic the structure of the natural extracellular matrix. There have been some attempts to fabricate such micro/nanostructures for biomedical applications such as tissue engineering scaffolds [35e38], implant surfaces [39e41], as well as blood-contacting materials [42]. Tan et al have produced micro-and nanoscale structures by depositing nanostructured hydroxyapatite on a microscale architecture created by microfabrication technology and these structures enhances some selective cellular functions [37].…”
Section: Introductionmentioning
confidence: 99%
“…Red blood cells may hemolyze when contacting with implant materials and thus cause eventually failure [34]. Therefore, for evaluating blood compatibility and biocompatibility, it is of vital importance to investigate the hemolysis ratio of the material.…”
Section: Blood Compatibility Of Oriented Plamentioning
confidence: 99%